Parenting Psikoedukasi Dalam Mendukung Perkembangan Sosial Dan Emosional Anak Usia Pra Sekolah Di Kota Surakarta - Insiyah Insiyah; Endang Caturini Sulistyowati (Poltekkes Kemenkes Surakarta, 2019)
Background: Children in kindergarten are experiencing rapid growth and development. Supporting child development is not only the responsibility of the government but also the responsibility of parents, teachers and the surrounding community. Parents are expected to have a good understanding of the psychological child so that they can provide care and education that allows children to grow and develop according to their age. This study aims to determine the effect of parenting psychoeducation on the social and emotional development of pre-school children. Methods: This research used the method of